3D-Printed Silk Fibroin Mesh with Guidance of Directional Cell Growth for Treating Pelvic Organ Prolapse - Zheng, Zili; Wang, Min; Ren, An; Cheng, Zhangyuan; Li, Xiangjuan; Guo, Chengchen (ACS biomaterials science & engineering, 2025)
Damages to the supportive structure of the pelvic floor frequently result in pelvic organ prolapse (POP), which diminishes the quality of life. Surgical repair typically involves mesh implantation to reinforce the weakened tissues. However, the commonly used polypropylene (PP) mesh can lead to severe complications due to the mechanical mismatch of the mesh with the pelvic tissues. In this study, 3D-printed silk fibroin (SF) meshes are developed and optimized through cryogenic 3D printing followed by post-stretching treatment to enhance mechanical properties and biocompatibility for POP repair. Rheological analysis shows that the 30 wt % SF-based ink exhibited a zero shear viscosity of 1838 Pa·s and shear-thinning behavior, ensuring smooth extrusion during 3D printing. During the cryogenic incubation following 3D printing, self-assembly of SF occurs with the formation of β-sheet structures, leading to robust constructs with good shape fidelity. The post-stretching treatment further improves SF chain alignment and fibrilization, resulting in enhanced mechanical performance and a microstrip surface that promotes cell attachment, alignment, and differentiation. The SF mesh with a post-stretching ratio of 150% shows an ultimate tensile strength of 1.49 ± 0.14 MPa, an elongation at break of 104 ± 13%, and a Young’s modulus of 5.0 ± 0.1 MPa at a hydrated condition, matching the properties of soft pelvic tissues. In vitro studies show that post-stretched SF meshes facilitated better cell alignment and myogenic differentiation than PP meshes. In vivo assessments demonstrate enhanced biocompatibility of the SF meshes, with better cellular infiltration and tissue integration than PP meshes in the long-term implantation, showing potential as a safe, effective alternative to traditional synthetic meshes for POP repair and other clinical applications.